The bryophyte community as bioindicator of heavy metals in a waterfall outflow - Narin Printarakul; Weeradej Meeinkuirt (Scientific Reports, 2022)
Abstract The species diversity and heavy metal accumulation in bryophytes were determined in Huay Pah Lahd stream in Doi Suthep-Pui National Park, Thailand. Eight bryophytes from two major taxonomic groupings (epilithic mosses and liverworts) were investigated. Of these, Fissidens crispulus var. crispulus was the most dominant taxon with an importance value (IV) of 28.98%, while Ectropothecium zollingeri, Claopodium prionophyllum, and Hyophila involuta were also dominant taxa with IV ≥ 10%. Scopelophila cataractae, a rare moss species with the lowest IV (0.91%) had the greatest capacity to accumulate metals in tissue, particularly Fe, Zn, Cd and Cu in protonemata (8026.7, 1187.2, 16.9 and 530.1 mg kg−1, respectively). The highest enrichment factors (EFs) of Zn, Cd and Cu (5.3, 2.4 and 0.9, respectively) were also found in S. cataractae, while the highest EFMn (1.1) was found in H. involuta. Enrichment factors of most heavy metals were < 5 from the study bryophytes, which suggests that natural processes were the key source of heavy metals. Dilution effects caused by increased water volume during the rainy season may be responsible for low pollutant loads and the maintenance of good water quality in this waterfall stream, which is favorable for biota and general environmental health.